Fatigue Fracture Properties Of Wood Plastic Composites - Nordin, Mohd Nur Azmi; Makino, Yuta; Goda, Koichi; Ito, Hirokazu (Society of Fiber Science and Technology, 2015)
Fatigue fracture properties of wood plastic composites (WPC) were investigated.The material was based on a wood flour/polypropylene (PP) master batch,and prepared to be 30wt% and 50wt% wood flour contents by the addition of PP pellets.First,kneading temperature and screw speed of a uni-axial extruder were changed in some conditions,and 190°C and 20rpm were decided from tensile test of the injection-molded WPC specimens as the optimum manufacturing conditions.Next,tensile and fatigue tests were carried out for WPC specimens with 30wt% and 50wt% wood flour contents.The resultant tensile strength and fatigue life were largely improved as compared to neat PP specimens.When a lump of the master batch remained in the WPC specimen,the strength and life were reduced.It should be noted that,while fatigue life of the neat PP specimens was only 10 to 102 cycles to failure range at 30MPa maximum cyclic stress,those of WPC specimens with 30wt% and 50wt% contents were drastically extended to 103 to 104,and 105 to 106 cycles to failure,respectively.It was estimated that the major cause of fatigue damage in WPC specimens was craze occurring in the matrix,which initiated near the specimen surface,extended into the inner, and finally led to the unstable fracture.